Enhanced Anaerobic Biogas Production From Wheat Straw by Herbal-Extraction Process Residues Supplementation - Xi, Yonglan; Liu, Yang; Ye, Xiaomei; Du, Jing; Kong, Xiangping; Guo, Dong; Xiao, Qingbo (Frontiers in Bioengineering and Biotechnology, 2021)
Trace metals are essential constituents of cofactors and enzymes and that their addition to anaerobic digesters increased methane production. Many trace elements are contained in herbal-extraction process residues(HPR). The present study concerns the effect of six kinds of HPR were as additives respectively in the anaerobic digestion of wheat straw on the biogas and methane production. The ratios of HPR residues /wheat straw (based on total solids (TS), of wheat straw) were 3%, 5% and 10%, respectively. The digesters at 37±1℃ water batch during 30 days anaerobic digestion. The highest biogas productivity was achieved with when treated with 10% Psoudo-ginseng residues(PGR), which yielded 337ml/g TS biogas and 178ml/g TS methane. Cumulative production of biogas and methane increased by 28% and 37% compared to the production achieved in control. These results suggest that PGR is an effective Chinese medicine residues to enhance the production of methane.